Periphytic diatoms (Bacillariophyta) in streams from three Conservation Units of central Brazil: Pinnularia Ehrenberg - FRANÇA, Alline Alves (Universidade Federal do Pará, 2019)
This study aimed to survey the genus Pinnularia Ehrenberg (Bacillariophyta) in five preserved streams located in three conservation units (Brasília National Park, Chapada dos Veadeiros National Park and Terra Ronca State Park). Periphyton was collected in different substrata during the dry and rainy seasons (years 2012 to 2013), totalizing 25 sample units. Altogether, 23 taxa were identified, being P. subanglica, P. angustivalvaand P. butantanum the most frequent. Pebble and sand were the richest substrates, with nine taxa each. Among the 23 taxa reported, 13 are cited for the first time for the central Brazil: P. angusta var. angusta, P. angustivalva, P. butantanum, P. divergens var. biconstricta, P. divergens var. mesoleptiformis, P. gibba var. subundulata, P. paulensis, P. persudetica var. persudetica, P. subgibba var. angustarea, P. subgibba var. capitada, P. superpaulensis, P. viridiformis var. minor and P. undula var. undula.